Healing Carbon Fiber/Polymer Interface by Resistive Heating. Issue 3 (March 2014) - Wang, Rongguo; Cao, Zhenxing; Hao, Lifeng; Jiao, Weicheng; Yang, Fan; Liu, Wenbo
Interface is the key region which determines, to a great extent, the set of properties of all heterogeneous systems, including composite materials. We reported interface healing of carbon fiber reinforced thermoplastic composite material via resistive heating. The carbon fiber, T700 carbon fiber, with a resistivity of 1.66 × 10 3 Ω·cm was used as the heating element while the matrix is polyarylether sulfone with cardo. Micro-droplet experiment was used to study the interface strength before and after heating to determine the healing efficiency. The measurement shows (experimental results show) that resistive heating is an efficient way to heal cracks near interface.